Modernized algorithm and results of the syntheses of the systems to stabilization’s of the cruising moving the plane - Блохін, Л.М.; Білак, Н.В. (Proceedings of National Aviation University, 2005)
It Is offered modernised algorithm of the syntheses of the optimum structures of the complex system to stabilisation of the plane in cruising flight in transport echelon at account only casual outraging motion factor. On practical example of the syntheses of the optimum structures of the system to stabilisation of the lateral moving the plane in cruising flight and got result is shown that only to account of the necessary optimum processing flow to on-board navigational information, possible provide competitiveness of the motion plane in echelon.